2008
DOI: 10.1177/0883073808314362
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Findings in Infants With Deformational Plagiocephaly

Abstract: This study evaluates the neurologic profiles of infants with deformational plagiocephaly. Forty-nine infants with deformational plagiocephaly between the ages of 4 and 13 months (mean age, 8.1 months) are evaluated, along with 50 age-matched control subjects (mean age, 8.1 months). A modified version of the Hammersmith infant neurologic assessment was performed on each infant. A caregiver completed a questionnaire regarding the infant's prematurity, development, and health to date. Results are analyzed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…39,46 More recently, however, studies have built a possible association between disruptions in infant development and PP. 10,21,28,30,63 Multiple reports over the past decade have pointed to links between PP and abnormal ophthalmological findings, auditory processing, and motor development. 4,10,25,27,28,35,44,47,62,63,68 Two case-controlled studies, by Speltz et al 63 and Fowler et al, 21 found significant variability in gross motor development and body tone.…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…39,46 More recently, however, studies have built a possible association between disruptions in infant development and PP. 10,21,28,30,63 Multiple reports over the past decade have pointed to links between PP and abnormal ophthalmological findings, auditory processing, and motor development. 4,10,25,27,28,35,44,47,62,63,68 Two case-controlled studies, by Speltz et al 63 and Fowler et al, 21 found significant variability in gross motor development and body tone.…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…Although there have been no rigorous prospective studies to address this concern, there is currently no evidence to suggest that positional skull deformity causes developmental delays. 8,[16][17][18] There has been some early motor skill developmental delay of all infants placed supine related to upper body strength and rolling over, which resolves over time. 19 Long-term follow-up studies have primarily been retrospective and questionnaire in nature and have not noted delays in cognitive or neurologic function.…”
Section: Introductionmentioning
confidence: 99%
“…5 Most of these deformities improve spontaneously during the first few months of life if the infant does not rest his or her head predominantly on the flattened area of the skull. If the infant continues to rest his or her head on the flattened side of the occiput, an initially occipital plagiocephalic deformity may be perpetuated or worsened by gravitational forces [6][7][8] and will be referred to in the remainder of this report as positional skull deformity as it relates to otherwise normal infants. Plagiocephaly is less commonly caused by unilateral lambdoidal or unilateral coronal craniosynostosis, which is a progressive and potentially devastating condition that requires early detection and surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…Greater numbers of studies are confirming the correlation between positional plagiocephaly and neurodevelopmental delay seen in fine motor skills. 7,9,12,19 Whether the developmental delay or the plagiocephaly is the causative factor remains unanswered. The importance of regular repositioning and observed tummy time cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%